REAKTUALISASI AKTIVITAS RELIGIUS DI LANGGAR NURUL YAKIN DESA BUNIIN JAYA - Nazaruddin, Ahmad; Rizali, Ahmad; Mutthiah, Mutthiah; Agustina, Lita; Yuliana, Erpipin; Bayti, Raudatul (Al-Manba, 2024)
Buniin Jaya Village faces the problem of low community participation in religious activities at Langgar Nurul Yakin. This problem is caused by various factors such as the long distance between houses, inadequate road access, and the lack of religious figures who motivate the community. This study aims to reactualize religious activities in the village. The method used is Participatory Action Research (PAR), which involves the active participation of KKN students and villagers. Data were collected through interviews, group discussions, and observations. The results of the study showed that religious-based activities, such as the commemoration of the Prophet's Birthday, teaching the Koran, and the call to prayer competition, succeeded in increasing community participation in religious activities at Langgar Nurul Yakin. The atmosphere of the langgar, which was previously quiet, is now more lively, and residents are starting to be active in religious activities. This study suggests the formation of a langgar management to maintain the sustainability of religious activities at Langgar Nurul Yakin, Buniin Jaya village.